A Statistical Analysis of Gender Development in Ukrainian Regions - Akbash, K. S.; Pasichnyk, N. O.; Rizhniak, R. Ya. (Statistics of Ukraine, 2019)
A regional adaptation of the Gender Development Index (GDI) to the sub-national level is proposed. The purpose of the article is to show the regional differences in composite GDI indicators and gender differences in these indicators. GDI covers the areas of longevity, knowledge and a decent standard of living. The indicators of the dimensions “Long and healthy life” and “Standard of living” were taken from the UN methodology for calculating the regional GDI, and the indicator of the dimension of “Knowledge” was replaced by a more informative one in the national context.The regional variations in GDI indicators showed that the situation in the regions of Ukraine in the dimensions of “Knowledge” and “Standard of living” was significantly different, whereas “Long and healthy life” indicators differed, but not critically. Gender differences in the indicators show the following for all regions: all the indicators of the dimensions of “Knowledge” and “Long and healthy life” reflect some significant gender asymmetry towards women, and the indicators of the dimension of “Standard of living” reflect the significant asymmetry towards men. Nevertheless, despite this gender asymmetry of GDI indicators, in all the regions of Ukraine GDI is close to unity, which means that it reflects gender parity in human development of men and women. The human development indicators for men and women show significant regional variations. We can single out the situation in the city of Kyiv, the capital of Ukraine, where almost all the indicators in all the areas differ from the other regions. The article also analyzes the regions with low indicators and significant gender gaps, as the low indicators of dimensions determine the low value of human development, and gender differences in indicators affect the value of the overall indicator of gender development. Testing of the proposed methodology for adapting the GDI to the sub-national level will make it possible to clarify its indicators for each region and, as a result, to prepare sound political, economic and social recommendations in the human development context taking into account the gender factor.